Intra-Abdominal Tumor in an Undescended Testis with Acute Abdominal Pain and Histopathological Features Suggestive of Alveolar Rhabdomyosarcoma: A Case Report - Simarmata, Vinansius Vivaldo Dair (Jurnal Kesehatan dan Kedokteran, 2026)
Intra-abdominal tumors associated with undescended testis are rare and may present with nonspecific symptoms resembling acute abdominal conditions. In adults, untreated undescended testis can delay diagnosis because the affected testis is not located in the scrotum and may only become clinically evident after tumor enlargement or abdominal symptoms. Objective: This case report aims to describe an intra-abdominal tumor in a 27-year-old male with untreated undescended testis who presented with acute right lower abdominal pain and a mass in the right iliac region. Methodology: This study used a descriptive case report design. Data were collected retrospectively from patient history, physical examination, operative findings, macroscopic tissue documentation, and histopathological examination. The data were analyzed using a descriptive-narrative approach supported by relevant literature. Findings: The patient presented with persistent right lower abdominal pain, progressive abdominal mass, weight loss, decreased appetite, and a history of untreated undescended testis since birth. Physical examination revealed an asymmetrical scrotum, absence of the right testis in the scrotum and inguinal canal, and a solid immobile mass in the right iliac region. Orchidectomy was performed, and macroscopic examination showed a grayish-brown mass measuring 11 × 10 × 7 cm. Histopathological examination revealed a malignant lesion suggestive of alveolar rhabdomyosarcoma. Research Implications: This case emphasizes the importance of genital examination in male patients with unexplained acute abdominal pain. Intra-abdominal testicular or paratesticular tumors should be considered when an empty hemiscrotum or cryptorchidism history is present. Originality: This report presents an unusual case of untreated undescended testis associated with an intra-abdominal tumor and histopathological features suggestive of alveolar rhabdomyosarcoma.